The Interplay of Achievement Motive-Goal Incongruence and State and Trait Self-Control: A Pilot Study Considering Cortical Correlates of Self-Control - Schüler, Julia; Hofstetter, Jonas; Wolff, Wanja (Frontiers in Behavioral Neuroscience, 2019)
Objective: This study utilized different theoretical perspectives to better understand motor performance. We refered to concepts of achievement motive-goal incongruence and assessed cortical correlates of self-control. We assumed that more self-control is required when people act in conformance with an incongruent goal which, in turn, results in impaired performance. We considered the activation of a brain area associated with self-control (dLPFC) as a consequence of motive-goal incongruence. Furthermore, we analyzed whether trait self-control buffers the negative effects of achievement motive – goal incongruence. Method: Twenty-eight participants (17 women, mean age: 24 years), whose implicit achievement motives were assessed at the beginning of the study, performed a handgrip task in an achievement goal condition and in three incongruent conditions, while their dLPFC oxygenation was monitored continuously (using functional near-infrared spectroscopy, fNIRS). Results: None of the two-way interactions (motive × goal condition) reached significance. A significant three-way interaction (motive × trait self-control × goal condition) showed that trait self-control buffered the detrimental effects of incongruence on motor performance. The nature of the three-way interaction predicting dLPFC oxygenation was unexpected. Conclusions: Although our results have to be treated with caution due to a small sample size, we see them as an encouraging starting point for further research on the interplay between motive-goal incongruence and trait and cortical correlates of state self-control that we assume to be important to understand performance in strenuous tasks.